Radiative MHD flow of Casson hybrid nanofluid over an infinite exponentially accelerated vertical porous surface - Krishna, M. Veera; Ahammad, N. Ameer; Chamkha, Ali J. (Case studies in thermal engineering, 2021)
The radiative unsteady magnetohydrodynamic (MHD) flow of an incompressible viscous electrically conducting non-Newtonian Casson hybrid nanofluid over an infinite exponentially accelerated vertical moving porous surface under the influence of slip velocity in a rotating frame has been explored in this paper. Water and ethylene glycol mixture have been considered as a base Casson fluid. A steady homogeneous magnetic field is applied under the assumption of low magnetic Reynolds number. The ramped temperature and time varying concentration at the surface is made into consideration. First order consistent chemical reaction and thermal absorption are also considered. Silver and Titania nanoparticles are disseminated in base fluid water and ethylene glycol mixture to be formed as hybrid nanofluid. Laplace transformation technique is employed on the non-dimensional governing equations for the closed form solutions. Based on those outcomes, the expressions for non-dimensional shear stress, rates of heat and mass transfer are also evaluated. The graphical representations are presented to scrutinize the effects of physical parameters on the significant flow characteristics. The computational values of the shear stresses, rate of heat transfer and rate of mass transfer at the surface are tabulated by the different implanted parameters. The resultant velocity is increasing with an increasing in thermal and concentration buoyancy forces, whereas rotation and slip parameters have overturn result on it for both cases of uniform wall temperature and ramped wall temperature. Species concentration of Casson hybrid Ag-TiO2/WEG nanofluid is decreased with an increase in Schmidt number and chemical reaction parameter. The Nusselt number is increased with an increase in heat absorption at the surface. [Display omitted]